Gamification in education: Experience based on Ecuadorian diversity. - Sánchez Pacheco, Carlos Luis (Revista Universidad de Guayaquil, 2021)
This present article addresses Gamification as an educational practice as an experience in Ecuadorian diversity. We begin by outlining the characteristics of what is now described as Digital Culture and its implications for the school environment; then we analyze the consequent need for a change in pedagogical practices. Then, as an alternative to this change, we propose School Gamification, a strategy that consists of inserting elements and aesthetics of electronic games in the classroom to work the contents in a more enjoyable way, which motivates the player to discover new ways of staying in the education. Given the large number of people of all ages who are immersed in the world of games and the expressive results that the corporate sphere has already obtained, especially Marketing, with gamified practices, it is believed that this strategy can contribute to learning effective given its power to involve people through pleasant, challenging and intriguing tasks, under the label of missions. The article ends with the statement that, to implement gamification in pedagogical practices, teachers need to know and understand the logic of electronic games and how they work. Only then